2017
DOI: 10.1159/000481752
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin Induces Proliferation via Positive Activation of the PI3K/Akt, P38 MAPK Pathways and Promotes Differentiation Through Activation of the GPRC6A-ERK1/2 Pathway in C2C12 Myoblast Cells

Abstract: Background/Aims: Sarcopenia is characterized by an age-related decline in skeletal muscle plus low muscle strength and/or physical performance. Despite the clinical significance of sarcopenia, the molecular pathways underlying sarcopenia remain elusive. The recent demonstration that undercarboxylated osteocalcin (ucOC) favours muscle function related to insulin sensitivity and glucose metabolism raises the question of whether this hormone may also regulate muscle mass. The present study explored the promotive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 35 publications
1
64
2
3
Order By: Relevance
“…(20,28) The ucOC effect on muscle cells appears to involve the enhancement of GPRC6A expression. (18) In support, the expression of GPRC6A was increased by ucOC + insulin treatment in placebo EDL muscle compared with insulin alone. However, ucOC did not change GPRC6A expression in muscle from CS-treated animals, suggesting that the alteration of GPRC6A abundance is unlikely to be involved in the rescuing effect of ucOC.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 83%
See 2 more Smart Citations
“…(20,28) The ucOC effect on muscle cells appears to involve the enhancement of GPRC6A expression. (18) In support, the expression of GPRC6A was increased by ucOC + insulin treatment in placebo EDL muscle compared with insulin alone. However, ucOC did not change GPRC6A expression in muscle from CS-treated animals, suggesting that the alteration of GPRC6A abundance is unlikely to be involved in the rescuing effect of ucOC.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 83%
“…Furthermore, it was reported that the effect is also likely via an increase in the abundance of these signaling proteins, including the postulated ucOC receptor G protein‐coupled receptor, class C, group 6, member A (GPRC6A) (Supplemental Fig. S1) . However, the exact molecular mechanisms of ucOC on muscle insulin resistance, particularly GC‐induced insulin resistance, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that the COPS3 was overexpressed in bone metastasis tissues by immunohistochemistry, and the levels of phosphorylated p38 MAPK reduced in the COPS3‐knockdown cells. MAPK families, which had identified at least three major signaling pathway in mammals including MAPK/ERK, stress‐activated kinase/c‐Jun N‐terminal kinase, and p38 MAPK were responsible for regulating complex cellular processes such as proliferation, differentiation, and apoptosis . The decreased level of p‐p38 MAPK induced by COPS3 knockdown indicated that COPS3 may promote the PCa cells proliferation by activating the p38 MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PIK3IP1 acts as a negative regulator of PI3K (He et al, ; DeFrances et al, ). In addition, the PI3K/AKT signaling pathway plays an important role in cell proliferation (Ohashi et al, ; Liu et al, ). Therefore, we hypothesized that WDR13 may affect the differentiation of bovine MDSCs by affecting the PI3K/AKT signaling pathway.…”
Section: Introductionmentioning
confidence: 99%